LECTURERS' PERCEPTIONS OF TEACHING PRACTICES AND VOCATIONAL DEVELOPMENT IN THE LANGUAGE DEPARTMENT - Halim Dwi Putra; Diah Paramita Sari; Safra Apriani Z; Arita Destianingsih; Ari Satria (INOVISH JOURNAL, 2022)
Abstract: The Vocational Program is indeed a pre-educational program that aims to prepare students who can create competence and abilities in their industries, who are ready to work, and can compete globally. Differences in teaching Lecturers' perceptions still occur, resulting in the learning and teaching process being treated differently, as well as the influence of assessment standards on students with varying standards, particularly in the production of students' final projects. This study intends to determine lecturers' perceptions of teaching methods and vocational development in the language department, which will be useful in equating useful perceptions in output standards and assessments of students’ final project in Bengkalis Language Department- State Polytechnic of Bengkalis. This study was done during a period of online learning and a global pandemic quarantine time